Analyzing The Impact of Project-Based Learning STEAM Flipped Classroom on Computer Architecture and Organization Courses in Higher Education - Ekayana, Anak Agung Gde; Parwati, Ni Nyoman; Agustini, Ketut; Ratnaya, I Gede (Society of Visual Informatics, 2024)
This study examines the differences in students' creative thinking skills between the project-based learning STEAM Flipped Classroom and the direct learning STEAM Flipped Classroom model by paying attention to the role of academic self-efficacy as a moderator variable. The research population consists of students in informatics engineering study programs in the Denpasar area of Bali. The study used a quasi-experimental 2 x 2 factorial design. Data collection is carried out through questionnaires and test instruments. Data analysis used descriptive and inferential statistics, as well as analysis of covariance. The results showed a significant difference in students' creative thinking skills between those who learned with the STEAM Flipped Classroom project learning model and the STEAM Flipped Classroom direct learning model. In addition, there are differences in students' creative thinking skills based on the level of academic self-efficacy. The empirical application of the STEAM Flipped Classroom project model is proven to help students generate new ideas, develop ideas, and improve their thinking skills. However, the findings suggest that flexible thinking skills must be further enhanced. Students with high self-efficacy tend to be more proactive in providing constructive ideas in project-based learning activities. This research implies that it is necessary to actively motivate and share experiential stories with students who have low self-efficacy. In the future, I suggest that universities adopt the innovative learning model of project-based learning STEAM flipped Classroom to improve the creative thinking skills of informatics engineering students at the college level.